2023
DOI: 10.1002/lpor.202200847
|View full text |Cite
|
Sign up to set email alerts
|

Smoothing Energy Transfer Enabling Efficient Large‐Area Quasi‐2D Perovskite Light‐Emitting Diodes

Abstract: Electroluminescence (EL) efficiency of perovskite light-emitting diodes (PeLEDs) based on a few square millimeters has improved significantly in recent years. Nevertheless, the EL efficiency of PeLEDs would plunge once the active area is enlarged from a millimeter to even a subcentimeter due to the unsmooth energy transfer process among the edge region with numerous nonradiative recombination centers. Herein, an intriguing strategy is developed to realize high-quality quasi-2D perovskite thin film via tuning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Nowadays, researchers have used octylamine (OTAm), 1-naphthylmethylammonium (NMA), ethoxylated trimethylolpropane triacrylate (ETPTA), etc. as ligands of quasi-2D perovskite to reduce the defect state density of thin films and improve the performance of devices [7,94,130,[154][155][156][157][158][159] .…”
Section: Ligand Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, researchers have used octylamine (OTAm), 1-naphthylmethylammonium (NMA), ethoxylated trimethylolpropane triacrylate (ETPTA), etc. as ligands of quasi-2D perovskite to reduce the defect state density of thin films and improve the performance of devices [7,94,130,[154][155][156][157][158][159] .…”
Section: Ligand Engineeringmentioning
confidence: 99%
“…Song, Wang and Sun et al. [ 155 ] added hydroxylamine‐O‐sulfonic acid (ASC) to the precursor solution and found that sulfonic acid groups were good candidates for chelating Pb 2+ . By recording the variation of PL with rotating coating time, it can be seen that ASC can inhibit the rapid crystallization process of quasi‐2D perovskite.…”
Section: Efficiency and Stability Strategy Of Gpeledsmentioning
confidence: 99%